Posttraumatic Embitterment Disorder and Hwa-byung in the General Korean Population - Joe, Soohyun; Lee, Jung Sun; Kim, Seong Yoon; Won, Seung-hee; Lim, Jong Seok; Ha, Kyoo Seob (Psychiatry investigation, 2017)
Posttraumatic embitterment disorder (PTED) is characterized by states of "embitterment", characteristically similar to "Hwa-byung", which is a Korean culture-bound syndrome. The present study aimed to assess diagnostic relationships between PTED and Hwa-byung. A total of 290 participants completed our survey. PTED and Hwa-byung were diagnosed using a diagnostic interview and scale. Scales for depression, suicide ideation, and anger were used for evaluation. Fisher's exact tests and Mann-Whitney U tests were performed to evaluate diagnostic overlap between PTED and Hwa-byung, and associations of scale scores for depression, suicide ideation, and anger between the PTED, Hwa-byung, and non-diagnosed groups. Associations of these scales between the depressive and non-depressive groups, and suicidal and non-suicidal groups were also evaluated. Among the participants, 1.7% of the sample fit the diagnostic criteria for PTED and 2.1% fit the criteria for Hwa-byung. No individual fit the criteria for both. Anger scores were significantly higher in the Hwa-byung group than in the non-diagnostic group. There were not any significant differences in anger scores between the PTED and non-diagnostic groups. Depression scores were significantly higher in the PTED than in the non-diagnostic groups. In contrast, no significant differences were observed between depression scores in the Hwa-byung and non-diagnostic groups. These results suggest that PTED may be a disorder category that is distinct from Hwa-byung.